Temporary Stomas after Rectal Cancer Resection; Predilection of Being Permanent and Predictors of Complications? - Metwally, Islam H.; Abdelkhalek, Mohamed; Zuhdy, Mohammad; Elbalka, Saleh S. (Journal of Coloproctology, 2023)
Stomas are essential for colorectal surgery and are widely used not only for selected cases for bowel obstructions but also in rectal cancer operations to divert stool away from low rectal anastomosis. On the other hand, complications with stomas/ stomas reversal are not uncommon. In this study, we aimed at studying the frequency and the predictors of temporary stomas being permanent, and the contributing factors of surgical stoma/stoma closure related complications. In our cohort, only about 40% of the patient closed their initially planned temporary stomas. The occurrence of intestinal leak, wound sepsis, or any type of morbidity with 30 days of operation were significant predictors of permanent stomas. In addition, alarmingly although Hartmann's procedure was uncommon in our practice, only 9% of those who underwent Hartmann's have had it reversed. Moreover, the only factor that significantly increased stoma related complications was having an end colostomy. There was a tendency toward late closure of stomas with median 8.2 months, however early closure did not correlate to complications. In conclusion, further studies are needed to delineate the low rate of stoma closure. Patients who develop postoperative complications, even wound sepsis, would be at a higher risk of living with permanent stomas. Hartmann's procedures are commonly associated with stoma problems, and reluctance to reverse the stomas.
Keywords: Rectal cancer; Proctectomy; Hartmann's procedure; Stoma